Agroforestry in Lushoto, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
A lot of work has been going on in the CCAFS Climate Smart Villages in Lushoto, Tanzania. Farmers have been engaging in agroforestry, farmer learning events, improved land management and use of indigenous knowledge in weather forecasting. These images showcase activities at the site. Photos P. Kimeli (CCAFS)